In Vitro Bulbification of Five Lily Varieties: An Effective Method to Produce Quality Seeds and Flowers - Yoiner K. Lapiz-Culqui; Jegnes Benjamín Meléndez-Mori; Gerardo Mállap-Detquizán; José Jesús Tejada-Alvarado; Nuri Carito Vilca-Valqui; Eyner Huaman-Human; Manuel Oliva; Malluri Goñas (International Journal of Agronomy)
Lilies are one of the most important, beautiful, and economically valuable flowers in the world. Lilium is regarded as a popular floral trade cut flower, so viable protocols are needed to provide seed production, multiplication, and preservation. In vitro protocols allow for rapid large-scale production and rejuvenation of planting material, but to be a commercially viable multiplication method, the procedure must allow for rapid production of viable, true-to-type plants quickly. The objective was to evaluate the in vitro production of microbulbs of five lily varieties (Lilium “Champion Diamond,” Lilium “Yellow Diamond,” Lilium “Batavus,” Lilium “Hyde Park,” and Lilium sp.) using different concentrations of 6-benzylaminopurine (0, 0.5, 1.0, 1.5, 1.5, and 2.0 mg L−1 BAP) and to determine the commercial quality (flowering) of the plants grown from the seed obtained. Results from the micropropagation phase show Lilium “Batavus” and Lilium “Hyde Park” varieties had better in vitro responses, especially when grown with 1.0 and 1.5 mg L−1 BAP, respectively. Plants (of all varieties) grown from microbulbs showed positive growth and generally resulted in commercially viable flower production. Finally, the results of this study support the use of bulb scales as an alternative for obtaining vegetative seeds with high potential for lily cultivation.